Charged-particle nuclear modification factors in XeXe collisions at √sNN=5.44 TeV - Sirunyan, A. M.; Tumasyan, A. R.; Adam, Wolfgang; Ambrogi, Federico; Asilar, Ece; Md. Ali, Mohd. Adli (Springer Verlag, 2018)
The differential yields of charged particles having pseudorapidity within |η| < 1 are measured using xenon-xenon (XeXe) collisions at √sNN = 5.44 TeV. The data, corresponding to an integrated luminosity of 3.42 µb −1 , were collected in 2017 by the CMS experiment at the LHC. The yields are reported as functions of collision centrality and transverse momentum, pT, from 0.5 to 100 GeV. A previously reported pT spectrum from proton-proton collisions at √ s = 5.02 TeV is used for comparison after correcting for the difference in center-of-mass energy. The nuclear modification factors using this reference, R∗ AA, are constructed and compared to previous measurements and theoretical predictions. In head-on collisions, the R∗ AA has a value of 0.17 in the pT range of 6–8 GeV, but increases to approximately 0.7 at 100 GeV. Above ≈6 GeV, the XeXe data show a notably smaller suppression than previous results for lead-lead (PbPb) collisions at √sNN = 5.02 TeV when compared at the same centrality (i.e., the same fraction of total cross section). However, the XeXe suppression is slightly greater than that for PbPb in events having a similar number of participating nucleons.